Effects of Alkalinity Exposure on Antioxidant Status, Metabolic Function, and Immune Response in the Hepatopancreas of Macrobrachium nipponense - Shubo Jin; Mingjia Xu; Xuanbin Gao; Sufei Jiang; Yiwei Xiong; Wenyi Zhang; Hui Qiao; Yan Wu; Hongtuo Fu (MDPI AG, 2024)
The oriental river prawn Macrobrachium nipponense is an important freshwater economic species in China, producing huge economic benefits. However, M. nipponense shows lower alkali tolerance than fish species, thus genetic selection is urgently needed in order to improve alkali tolerance in this species. In the present study, the effects of alkalinity exposure on the hepatopancreas of M. nipponense were measured under the alkali concentrations of 0 (control), 4, 8, and 12 mmol/L with the exposure time of 96 h through histological observations, measurement of antioxidant enzymes, metabolic profiling analysis, and transcriptome profiling analysis. The present study identified that the low concentration of alkali treatment (<4 mmol/L) did not result in morphological changes in the hepatopancreas and activity changes in antioxidant enzymes, while high-alkali treatment (>8 mmol/L) damaged the normal structures of the lumen and vacuoles and significantly stimulated the levels of superoxide dismutase, catalase, and total antioxidant capacity, indicating these antioxidant enzymes play essential roles in the protection of the body from the damage caused by the alkali treatment. Metabolic profiling analysis revealed that the main enriched metabolic pathways of differentially expressed metabolites in the present study were consistent with the metabolic pathways caused by environmental stress in plants and other aquatic animals. Transcriptome profiling analysis revealed that the alkali concentration of <8 mmol/L did not lead to significant changes in gene expression. The main enriched metabolic pathways were selected from the comparison between 0 mmol/L vs. 12 mmol/L, and some significantly up-regulated genes were selected from these metabolic pathways, predicting these selected metabolic pathways and genes are involved in the adaptation to alkali treatment in M. nipponense. The expressions of Ras-like GTP-binding protein, Doublesex and mab-3 related transcription factor 1a, and Hypothetical protein JAY84 are sensitive to changes in alkali concentrations, suggesting these three genes participated in the process of alkali adaptation in M. nipponense. The present study identified the effects of alkalinity exposure on the hepatopancreas of M. nipponense, including the changes in antioxidant status and the expressions of metabolites and genes, contributing to further studies of alkali tolerance in this species.